Multi‐tissue cytogenetic analysis for the diagnosis of mosaic Down syndrome: A case report. Issue 4 (8th April 2022) - Moncada Arita, Wilberg A.; Perdomo Domínguez, Eduardo Smelin; Rivera Caballero, Astrid Yohaly; Espinoza‐Moreno, Nelson A.; Zavala Galeano, Mauricio E.; DuPont, Barbara R.; Ramos‐Zaldívar, Héctor M.
Abstract: Less than one percent of individuals with Down syndrome exhibit mosaicism, a biological phenomenon that describes an individual who has two or more genetically distinct cell lines. The percentage of mosaicism in different tissues can impact the presence of clinical findings and hinder cytogenetic diagnosis. We report a case of mosaicism for trisomy 21 diagnosed after multi‐tissue cytogenetic analysis of peripheral blood and buccal mucosa, associated with significant intellectual disability, dysmorphic facial features, congenital heart defects, macropenis, and imperforate anus. Abstract : A multi‐tissue approach should be utilized in patients with high suspicion of mosaic Down syndrome following a negative karyotype. This could include analysis of skin, peripheral blood, and buccal mucosa cells. In this case, the proportion of mosaicism was not a direct correlate to phenotype severity.